A Theoretical Proposed Frameworks to Satisfied Sustainability in Iraq's Building Industry - Altuma, Mohanad Ibrahim; Alrikabi , Azhar Abed Mohisen (Indonesian Journal Publisher, 2024)
The current research introduces a theoretical framework developed to integrate sustainability ideas into the construction sector. The suggested framework, established on the sustainable triple-bottom paragraph concept, encompasses resource preservation, expensive reduction, and planning that emphasizes the well-being. After conducting a comprehensive literature assessment, each concept related to strategies and methodologies applicable throughout the life cycle of construction projects is elucidated, accompanied by many case examples to illustrate the approaches. The framework will enable designers to achieve a suitable equilibrium among economic, cultural, and environmental considerations, transforming the mindset of construction practitioners regarding the information utilized in evaluating building projects, thus promoting the sustainability of the Iraqi construction industry.